Analisis Implementasi Kebijakan Jaminan Produk Halal pada Produk Makanan di Kota Tangerang - Syahril Anwarudin, Muhamad; Stiawati, Titi; Rizkiyani, Tiwi (PUBLICNESS: Journal of Public Administration Studies, 2024)
Law Number 33 of 2014 concerning Halal Product Guarantee aims to provide comfort, security, safety, and availability of halal products for the people of Indonesia in consuming and using products. After the law was enacted, the obligation of halal certification for business actors changed from voluntary to mandatory, but there are still many business actors who do not have halal certificates. This research focuses on analyzing the implementation of the Halal Product Guarantee Policy on Food Products in Tangerang City. This study aims to determine and analyze how the implementation of the Halal Product Guarantee policy on food products in Tangerang City. The problem that occurs and is studied by researchers is that food products in Tangerang City have not been able to fulfill the principles of halal product guarantees, namely they have not been able to fulfill the principles of protection, have not been able to fulfill the principles of effectiveness and efficiency, and have not been able to fulfill the principles of professionalism. This research uses qualitative methods by analyzing the results of observation, interviews, and documentation. The results of the research using Soren C. Winter's policy implementation theory show that the implementation of the Halal Product Guarantee policy on food products in Tangerang City has not been fully implemented. Overall, this policy has not been able to run optimally in providing legal protection for products circulating in Indonesia in accordance with the policy objectives.